Because I Got High? Recreational Marijuana Legalization's Impact on Opioid Overdose Deaths - Denkyirah, Elisha Kwaku; March, Raymond J.; Rayamajhee, Veeshan; Yonk, Ryan M. (Southern economic journal, 2025)
We examine the effect of recreational marijuana legalization (RML) on opioid overdose deaths. Using several event studies and a two‐way fixed‐effects, difference‐in‐differences approach adapted to the methods developed by Callaway and Sant'Anna, we find a consistent negative relationship between RML and opioid overdose deaths. Our estimates show that RML is associated with a decrease of approximately 3.5 deaths per 100,000 individuals. We also find more significant treatment effects for states that implemented RML earlier. These findings remain consistent through a variety of robustness checks and provide insight for future opioid and marijuana policies.